(untitled) (Academicia Globe: Inderscience Research, 2022)
The article deals with the possibilities of theoretical enrichment of the professional competence of future teachers of musical performance based on international best practices, the development of creative thinking, independence, creativity, activism, and self-control of future teachers of musical performance. and the formation of their upbringing needs.Much attention is also paid to the development of the ability of future teachers of instrumental performance to apply the acquired knowledge in practice, without denying the competent approach to education, knowledge, skills, and abilities.